IMPROVING THE CAPABILITIES OF SMALL TO MEDIUM SIZED FIRMS IN THE SERVICES SECTOR OF THE NIGERIAN ECONOMY - Ijogun, O.B (2011)
The research context is built on the recognition of the macro level need for economic diversity in Nigeria, probing further reveals a micro level need for improvements in the kind of professional services required to facilitate projects that contribute towards the development of domestic infrastructure and ultimately overall economic advancement. The research focuses on how to improve capabilities of the chosen firm ‘Billing Cost Associates a firm of chartered quantity surveyors’. This firm is an ideal example of a thriving firm in the harsh nigerian context. This research was conducted in Nigeria through a series of interviews and less formal disscussions, numerous documents were also gathered. The motivation for this research as a stakeholder of the nigerian economy is to encourage others particularly those in power to increase the focus and efforts on diversifying the economy, particularly the Services and Manufacturing sectors which constitute a smaller proportion of the GDP compared to the oil & gas sector. Clearly Government officials, consultancy firms and the society should collectively support firms in other sectors of the Economy.